Structure of the CRISPR interference complex CSM reveals key similarities with cascade. - Rouillon, C; Zhou, M; Zhang, J; Politis, A; Beilsten-Edmands, V; Cannone, G; Graham, S; Robinson, C; Spagnolo, L; White, M (2013)
The Clustered Regularly Interspaced Palindromic Repeats (CRISPR) system is an adaptive immune system in prokaryotes. Interference complexes encoded by CRISPR-associated (cas) genes utilize small RNAs for homology-directed detection and subsequent degradation of invading genetic elements, and they have been classified into three main types (I-III). Type III complexes share the Cas10 subunit but are subclassifed as type IIIA (CSM) and type IIIB (CMR), depending on their specificity for DNA or RNA targets, respectively. The role of CSM in limiting the spread of conjugative plasmids in Staphylococcus epidermidis was first described in 2008. Here, we report a detailed investigation of the composition and structure of the CSM complex from the archaeon Sulfolobus solfataricus, using a combination of electron microscopy, mass spectrometry, and deep sequencing. This reveals a three-dimensional model for the CSM complex that includes a helical component strikingly reminiscent of the backbone structure of the type I (Cascade) family.